An Investigation of the Main Factors to be Considered in Cloud Computing Adoption in Australian Regional Local Councils - Ali, Omar; Soar, Jeffrey; Yong, Jianming (The journal of contemporary issues in business and government, 2015)
Technology plays an important role in helping organisations control quality and costs, and taking advantage of opportunities in a highly competitive and increasingly complex business environment. Cloud computing offers greater access to computing power, storage, software, and remote data centres through the web. This research aims to investigate the factors to be considered for cloud computing adoption by Australian regional councils. The research employed in-depth interviews with IT managers from selected local government councils. The major factors to be considered for the adoption of cloud computing were identified as Internet connectivity, data storage location, cost, integration, data back-up, provider dependability, employees’ knowledge, and transportability. The findings of this research may help managers increase their awareness about factors to be considered when planning to adopt cloud computing.